FGFR3 mutation causes abnormal membranous ossification in achondroplasia - Federico Di Rocco; Martin Biosse Duplan; Yann Heuzé; Nabil Kaci; Davide Komla‐Ebri; Arnold Münnich; Emilie Mugniery; Catherine Benoist-Lasselin; Laurence Legeai‐Mallet (2014)
FGFR3 gain-of-function mutations lead to both chondrodysplasias and craniosynostoses. Achondroplasia (ACH), the most frequent dwarfism, is due to an FGFR3-activating mutation which results in impaired endochondral ossification. The effects of the mutation on membranous ossification are unknown. Fgfr3Y367C/+ mice mimicking ACH and craniofacial analysis of patients with ACH and FGFR3-related craniosynostoses provide an opportunity to address this issue. Studying the calvaria and skull base, we observed abnormal cartilage and premature fusion of the synchondroses leading to modifications of foramen magnum shape and size in Fgfr3Y367C/+ mice, ACH and FGFR3-related craniosynostoses patients. Partial premature fusion of the coronal sutures and non-ossified gaps in frontal bones were also present in Fgfr3Y367C/+ mice and ACH patients. Our data provide strong support that not only endochondral ossification but also membranous ossification is severely affected in ACH. Demonstration of the impact of FGFR3 mutations on craniofacial development should initiate novel pharmacological and surgical therapeutic approaches.